Primary motor cortex of the parkinsonian monkey: altered neuronal responses to muscle stretch - Pasquereau, Benjamin; Turner, Robert S. (Frontiers in Systems Neuroscience, 2013)
Exaggeration of the long-latency stretch reflex (LLSR) is a characteristic neurophysiologic feature of Parkinson's disease (PD) that contributes to parkinsonian rigidity. To explore one frequently-hypothesized mechanism, we studied the effects of fast muscle stretches on neuronal activity in the macaque primary motor cortex (M1) before and after the induction of parkinsonism by unilateral administration of 1-methyl-4-phenyl-1,2,3,6-tetrahydropyridine (MPTP). We compared results from the general population of M1 neurons and two antidromically-identified subpopulations: distant-projecting pyramidal-tract type neurons (PTNs) and intra-telecenphalic-type corticostriatal neurons (CSNs). Rapid rotations of elbow or wrist joints evoked short-latency responses in 62% of arm-related M1 neurons. As in PD, the late electromyographic responses that constitute the LLSR were enhanced following MPTP. This was accompanied by a shortening of M1 neuronal response latencies and a degradation of directional selectivity, but surprisingly, no increase in single unit response magnitudes. The results suggest that parkinsonism alters the timing and specificity of M1 responses to muscle stretch. Observation of an exaggerated LLSR with no change in the magnitude of proprioceptive responses in M1 is consistent with the idea that the increase in LLSR gain that contributes to parkinsonian rigidity is localized to the spinal cord.